2022
DOI: 10.1155/2022/8735551
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Four-Gene Signature and Nomogram for Predicting the Overall Survival of Papillary Thyroid Cancer

Abstract: Background. Although the prognosis of papillary thyroid cancer (PTC) is relatively good, some patients experience recurrence or distant metastasis after thyroidectomy and progress to radioactive iodine refractory stage. Therefore, accurate prediction of clinical outlook can aid to screen out the minority of patients with poorer prognosis and avoid excessive treatment in low-risk patients. Methods. The RNA-seq and clinical data of PTC patients was downloaded from the Gene Expression Omnibus (GEO) and the Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…ABI family member 3 binding protein (ABI3BP) is an ECM protein expressed in multiple organs, including the heart, kidney, lung, pancreas, and placenta, with low or variable expression in the spleen, liver, brain, bone, and skeletal muscle ( 98 ). ABI3BP expression has been associated with many physiological and pathological processes ( 99 ), and it is well known for its role in multiple cancer types, acting as a tumor suppressor by inhibiting cancer cell proliferation and migration and promoting cellular senescence ( 100 104 ). The role of ABI3BP in lung cancer has been investigated only recently and it has been indicated that this molecule is downregulated in the lesions compared to normal lung tissue and it gradually decreases as lung cancer progresses ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…ABI family member 3 binding protein (ABI3BP) is an ECM protein expressed in multiple organs, including the heart, kidney, lung, pancreas, and placenta, with low or variable expression in the spleen, liver, brain, bone, and skeletal muscle ( 98 ). ABI3BP expression has been associated with many physiological and pathological processes ( 99 ), and it is well known for its role in multiple cancer types, acting as a tumor suppressor by inhibiting cancer cell proliferation and migration and promoting cellular senescence ( 100 104 ). The role of ABI3BP in lung cancer has been investigated only recently and it has been indicated that this molecule is downregulated in the lesions compared to normal lung tissue and it gradually decreases as lung cancer progresses ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…While numerous studies have developed lncRNA-related nomogram models to predict tumor development and progression, the majority have focused on predicting early-stage micrometastasis 21 , 22 . Our research, however, is primarily focused on the distant metastasis of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A calibration curve was used to test the agreement between the actual results and model predictions according to the Hosmer–Lemeshow test. To compare the accuracy, we calculated the consistency index (c-index) and restricted mean survival (RMS) of the published models ( Guo et al, 2022 ; Qin et al, 2022 ; Ding et al, 2022 ; Liu et al, 2022 ; Shan et al, 2022 ) and the model we developed.…”
Section: Methodsmentioning
confidence: 99%